Effects of shrub encroachment on grassland community and soil nutrients among three typical shrubby grasslands in the alpine subhumid region of the Qinghai-Tibet Plateau, China - Yu, Shuhan; Liu, Xiaolong; Chen, Xueling; Sun, Meiling; Cao, Yongqiang; Hu, Jinjiao; Yang, Lixue; Hu, Jian (Frontiers in Ecology and Evolution, 2022)
The alpine meadows are distributed widely and play a vital role in ecosystem service functions on the Qinghai-Tibet Plateau (QTP). Under the combined effect of climate change and overgrazing, shrubs display an apparent expansion trend, leading to the shrinking of alpine meadows, and directly affecting the structure and function of grassland ecosystems. However, the effects of shrub encroachment on the plant community and soil nutrients of alpine grassland ecosystems still need to be clarified. We aimed to determine differences in vegetation characteristics and nutrient distribution along the soil profile between shrub patches and their adjacent grassland at three sites, which were three typical types of shrub-encroached grassland, including Spiraea alpina Pall. (SA), Lonicera tubuliflora Rehd. (LT), and Salix cupularis Rehd. (ST). The results showed that shrub invasion changed the plant community structure of alpine grassland ecosystems, and shrub type was the critical factor driving this alteration. The expansion of the three shrubs reduced grassland species diversity. Shrub encroachment in SA positively impacted vegetation biomass but significantly decreased the soil organic content (SOC)and total nutrients. Shrub invasion in the ST had the most substantial impact on vegetation and soil, resulting in significantly lower nutrient content in shrubs than in grassland patches. The effect of LT was a significant reduction in vegetation biomass but no significant changes in biodiversity or soil nutrients. Grassland patches were more strongly correlated than shrub patches for SA and LT, while the opposite was true for ST. Vegetation characteristics were correlated least with soil nutrients for SA, while ST was most correlated, and LT was between them. Soil nutrients show more positive correlations with vegetation, enzyme activity, and microbial biomass in deeper soils (20-100 cm) than in shallow soils (0-20 cm). The deeper the soil layer is, the more significant the positive correlations in the shrub patches. Our findings indicated that shrubs play critical roles in the dynamics of vegetation patterns and soil environments for managing and sustainable utilization of shrubby alpine grasslands.